Material modelling of rubber coated fabrics employed in the design of innovative ship rescue systems - Ilias, Zilakos (Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2018)
The computational modelling of pneumatic structures requires accurate and numerically robust representation of the mechanical response of the composite system used in their fabrication. In this thesis, a new constitutive law is developed for describing the mechanical behaviour of rubber coated fabrics under uniaxial and biaxial loading. Within the continuum framework of orthotropic hyperelasticity, the adopted modelling approach directly accounts for both plane stress and incompressibility conditions. The candidate material is used in the fabrication of prototype inflatable devices which are envisaged to be used in emergency situations at sea, providing reserve buoyancy to damaged ships, preventing capsizing and/or sinking, along with lifting wreckages from the seabed. The proposed strain energy density function is based on an integral form of a hyperbolic trigonometric function. A stepwise procedure, partially guided by the linear response of the material, was followed to determine the argument-expression of the trigonometric function. The material parameters involved in the formulation of the strain energy density function were simultaneously fitted to uniaxial and biaxial tension tests data, carried out at various stress ratios, using a gradient based optimization scheme. The computed material parameters were found to satisfy the positive definiteness constraints of the linear elasticity tensor. Furthermore, the numerical stability of the material model was also examined since this a prerequisite for the reliability of a FE simulation. The findings suggest that no numerical instabilities should be encountered for the applications examined in this work. The proposed strain energy density function was employed in the derivation of the stress and elasticity tensors for use in the numerical implementation of the constitutive model into the finite element code ABAQUS. Verification and validation tests of the required material subroutine were carried out respectively by single elements tests and simulations of the actual test pieces used in the uniaxial and biaxial tension tests. The final chapter of the thesis presents certain structural applications of the salvage unit which demonstrate the utility and effectiveness of the constitutive law and also highlight specific aspects of its response under loading. In particular, a shell FE analysis of the spherocylindrical unit under internal pressure has shown that the bending at the cylinder to sphere transition is very localised and therefore its response is close to that of a membrane structure. The FE simulation of the latter stages of inflation of the salvage devices inside an actual double bottom structure resulted in good agreement with proof of concept tests under dry conditions, in terms of global response and contact areas. Finally, the behaviour of the inflatables under buoyancy loading was simulated and studied, leading to useful conclusions concerning the evolving stress state in the device under increased contact with the surrounding metal structure.